1994
DOI: 10.1016/0026-0495(94)90027-2
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive changes in transmembrane transport and metabolism of triiodothyronine in perfused livers of fed and fasted hypothyroid and hyperthyroid rats

Abstract: The transport and subsequent metabolism of triiodothyronine (Ts) were studied in isolated perfused livers of euthyroid, hypothyroid, and hyperthyroid rats, both fed and 48-hour-fasted. Ts kinetics (transport and metabolism) during perfusion were evaluated by a two-pool model, whereas the metabolism of T3 was also investigated by determination of T, breakdown products by chromatography of medium and bile. For comparison of groups, metabolism was corrected for differences in transport. Transport parameters in fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
1

Year Published

1997
1997
2007
2007

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 38 publications
0
4
1
Order By: Relevance
“…Previous observations with the use of isolated perfused rat liver indicate that hepatic uptake of T 3 is decreased in hyperthyroid animals (7), whereas the present findings suggest no effect of hyperthyroidism on hepatic T 4 uptake. A different regulation of hepatic uptake of T 4 and T 3 is consistent with the existence of separate transporters for T 4 and T 3 (22,29).…”
Section: Discussioncontrasting
confidence: 85%
See 2 more Smart Citations
“…Previous observations with the use of isolated perfused rat liver indicate that hepatic uptake of T 3 is decreased in hyperthyroid animals (7), whereas the present findings suggest no effect of hyperthyroidism on hepatic T 4 uptake. A different regulation of hepatic uptake of T 4 and T 3 is consistent with the existence of separate transporters for T 4 and T 3 (22,29).…”
Section: Discussioncontrasting
confidence: 85%
“…Both in humans and in rats, the liver plays a major role in plasma T 3 production (13). Previous experiments in our laboratory have shown that liver uptake of T 3 is decreased in hyperthyroid rats (7). The aim of this study was to investigate whether thyroid state influences the mRNA levels for hepatic T 4 transporter(s) by use of the X. laevis oocyte expression system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data suggest an adaptation mechanism at the cellular level to maintain tissue T3 levels when T3 supply is abnormal (198). When expression of mRNA of thyroid hormone transporters in rat liver was studied, using Xenopus laevis oocytes as expression system, no thyroid state-dependent differences were seen in the expression of these transporters, not excluding, however, any regulation of transporter activity at the translational or post-translational level (199).…”
Section: Plasma Membrane Transport Is Subject To Regulationmentioning
confidence: 87%
“…In livers of hyperthyroid rats, uptake of T 3 was decreased and T 3 metabolism was increased. These data suggest an adaptation mechanism at the cellular level to maintain tissue T 3 levels when T 3 supply is abnormal (198). When expression of mRNA of thyroid hormone transporters in rat liver was studied, using Xenopus laevis oocytes as the expression system, no thyroid state-dependent differences were seen in the expression of these transporters, not excluding, however, any regulation of transporter activity at the translational or posttranslational level (199).…”
Section: Plasma Membrane Transport Is Subject To Regulationmentioning
confidence: 87%